2020
DOI: 10.33448/rsd-v9i10.8556
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias para a promoção do envelhecimento ativo no Brasil: uma revisão integrativa

Abstract: Objetivo: analisar as estratégias propostas no meio científico para a promoção do envelhecimento ativo no cenário brasileiro, e identificar as possíveis lacunas que o impedem de se tornar uma realidade. Método: revisão integrativa realizada nas bases de dados Scientific Eletronic Library (Scielo), Literatura Latino-Americana e do Caribe em Ciências da Saúde (Lilacs), e Pubmed, em Setembro 2020, com os descritores; envelhecimento saudável, bom envelhecimento, envelhecer bem, envelhecer saudável, envelhecimento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
(18 reference statements)
1
7
0
3
Order By: Relevance
“…In addition to possible limitations in relation to carrying out activities of daily living, elderly face several obstacles, including attitudinal, environmental, and institutional barriers, which prevent their full and equal participation in all aspects of life (Martins et al, 2020 ). When evaluating social participation, this study could observe an average score of 14.99 (74.9%) which demonstrates that there is a loss of social participation within this group, although it is still a regular average, since other studies suggest a significant loss in social participation of the elderly(O. Figueira et al, 2020 ), while reinforcing the importance of social interaction as a measure to promote QOL. A study carried out with 1691 elderly in Minas Gerais / Brazil obtained 63.4% in the average percentage of the social participation facet, indicating that the elderly in that study found fewer opportunities to participate in activities in the community.…”
Section: Discussionsupporting
confidence: 58%
“…In addition to possible limitations in relation to carrying out activities of daily living, elderly face several obstacles, including attitudinal, environmental, and institutional barriers, which prevent their full and equal participation in all aspects of life (Martins et al, 2020 ). When evaluating social participation, this study could observe an average score of 14.99 (74.9%) which demonstrates that there is a loss of social participation within this group, although it is still a regular average, since other studies suggest a significant loss in social participation of the elderly(O. Figueira et al, 2020 ), while reinforcing the importance of social interaction as a measure to promote QOL. A study carried out with 1691 elderly in Minas Gerais / Brazil obtained 63.4% in the average percentage of the social participation facet, indicating that the elderly in that study found fewer opportunities to participate in activities in the community.…”
Section: Discussionsupporting
confidence: 58%
“…The framework of the active aging policy [5] suggests a new paradigm, which sees older people as active participants in an age-integrated society and as active contributors as well as beneficiaries of development [4]. Active refers to continuous participation in matters, but not only being physically active, and health refers to well-being, therefore, policies and programs that increase the well-being and participation of older people in the matters they refer to are particularly welcome [12]. The agenda for sustainable development with 12 integrated and indivisible goals proposes a way to achieve these goals with a focus on the growing priority of promoting the well-being of older people worldwide [46].…”
Section: Sustainable Agingmentioning
confidence: 99%
“…Furthermore, the internationally validated Baecke-Old questionnaire [11] contemplates this approach. There is consensus in the academic literature on the benefit of the practice of individual and/or collective PA for the older population, both in health and in quality of life [12]. Being active helps older people to remain as independent as possible for the longest period of time, participating in physical activities (PAs), delaying functional decline, identifying strengths, personal values, and interests, and creating a full life [13].…”
Section: Introductionmentioning
confidence: 99%
“…Healthy aging with physical activityis the solution to the main challenges that population aging poses for the health system, and implies satisfaction with life and health, emotional and physical independence and vitality, significant factors for an independent life [5]. Aiming to increase active aging worldwide, the World Health Organization started in 2020 the decade of healthy aging [6]. Healthy aging is defined as the process of developing and maintaining functional skills in aging and it is fundamental as demographic aging and its challenges can only be achieved with the support of society as a whole [1], and of each individual de per se.…”
Section: Introductionmentioning
confidence: 99%
“…Depression in the older people is strongly associated with physical inactivity [10]. The practice of Physical Activity (PA) benefits the health of the older people [6]. PA, even with light exercises, is an important contribution to both physical and mental health, demonstrating benefits even in more severe mental disorders [11].…”
Section: Introductionmentioning
confidence: 99%